G179(P) Long Term Follow-Up For Paediatric Oncology Patients at a Paediatric Department of a General Hospital. (4th June 2013) - Murphy, SM; Husselbee, KM
Abstract : Aims: Establish how national Long Term Follow Up recommendations can be implemented locally in a paediatric department of a large general hospital. Establish the number of patients who currently have an end of treatment summary in their notes. Determine how many patients are attending appointments. Identify if the appropriate patients are attending clinics. Methods: The medical notes for all patients appointed to attend the long term follow up clinic over the preceding two years were reviewed (93 patients). It was noted whether each patient had an end of treatment summary present in their notes Attendance at clinic over the past two years was noted. Patients were assigned into different groups according to the 'Therapy-based recommended levels of follow-up'. 1 Results: The majority (91%) of patients did not have an end of treatment summary in their notes. The majority of patients were in treatment 'level 2' (47%).Those in levels 2&3 will require long term medically supervised follow-up (nurse led or GP if level 2). Attendance at clinic was noted & of those attending clinic, those with the best 'full time' attendance were those deemed to be 'level 2' patients. Followed by level 3 and 1 respectively. Conclusion: An 'End of Treatment Summary' should be implemented in the notes of all patients who have completed their treatment for childhood cancer. Review current attendance of those deemed to be level 2 or 3 patients with the view to implementing a postal questionnaire in order to re-engage patients currently lost to follow-up. Reference: Wallace, W Blacklay, A Eiser, et al. Developing strategies for long term follow up of survivors of childhood cancer. BMJ 2001;323:271-4.